PEMBUATAN GAME PUZZLE “DIGITUS” BERBASIS ANDROID - Christine Christine; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
In this game, player is asked to drag arrow to their pair. There are 2 modes in this game, i.e. one hand and two hands. 10 different stages for each mode. This game use multitouch features. Stage 2 to 10 have a minimum point to be able to open and play the next stage. This game has been tested by black box method, alpha testing and beta testing using a questionnaire through Google Form and Google drive to save Digitus game files. The results show that Digitus is fascinating to be played over and over again, how to play feature can be understood easily, and attractive design.